(untitled) (International journal of artificial intelligence, 2025)
This article provides a comprehensive analysis of the relationship between the quality of health services and the well-being of the population. The relationship between the effectiveness of modern health systems, the quality of service provision and population health indicators is highlighted on the basis of scientific literature. The impact of quality health services on the general well-being of the population, economic and social factors are also considered. The article provides recommendations for the development of the health system and improving the well-being of the population.